2017
DOI: 10.1140/epjb/e2017-80082-y
|View full text |Cite
|
Sign up to set email alerts
|

Continuum of many-particle states near the metal-insulator transition in the Hubbard model

Abstract: The strong coupling diagram technique is used for investigating states near the metal-insulator transition in the half-filled two-dimensional repulsive Hubbard model. The nonlocal third-order term is included in the irreducible part along with local terms of lower orders. Derived equations for the electron Green's function are solved by iteration for moderate Hubbard repulsions and temperatures. Starting iteration from Green's functions of the Hubbard-I approximation with various distances of poles from the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 42 publications
7
12
0
Order By: Relevance
“…It is worth noting that the dashed curve in this figure nearly coincides with the metal-insulator boundary found in Ref. [20], in which only diagrams (a), (b) and (e) in Fig. 1 were taken into account, that is only short-range spin and charge fluctuations were considered.…”
Section: Comparison With Results Of Other Methods and Sum Rulessupporting
confidence: 76%
“…It is worth noting that the dashed curve in this figure nearly coincides with the metal-insulator boundary found in Ref. [20], in which only diagrams (a), (b) and (e) in Fig. 1 were taken into account, that is only short-range spin and charge fluctuations were considered.…”
Section: Comparison With Results Of Other Methods and Sum Rulessupporting
confidence: 76%
“…A similar flattening of the spin-polaron band and a persistent DOS peak at the FL were observed in the t-J model [38,39]. In two dimensions (2D), the momentum dependence of the electron self-energy is rather strong [16,23,40], and the applicability of the DMFA ideas, in this case, is not evident. We argue that the peak at the FL (for brevity, the FL peak) may explain some peculiarities of photoemission spectra in the n-type crystal Nd 2−x Ce x CuO 4 [41,42,43,44].…”
Section: Introductionsupporting
confidence: 65%
“…Up to the constant factor χ(l ′ , τ ′ ; l, τ ) (3) coincides with the spin susceptibility. For calculating these quantities the SCDT [10,11,12,13] is used (a concise description of this diagram technique can be found in [40]). In this approach, the Fourier transform of Green's function (2) can be presented in the form…”
Section: Main Formulasmentioning
confidence: 99%
“…3 For other considered values of U transitions temperatures were found also to be close to those obtained in Ref. [3]. It can be concluded that short-range fluctuations play the main role in determining the locations of the transition curve in the considered parameter ranges.…”
Section: Results Of Calculationssupporting
confidence: 84%